Factors Associated with Stunting Among Children Under Five in the Kanigaran Community Health Center Catchment Area, Probolinggo City - Irma Kurniawati; Raden Maria Veronika Widiatrilupi (Griya Eka Sejahtera, 2026)
Background: Stunting remains a major public health challenge because it adversely affects children's physical growth, cognitive development, and future productivity. Identifying factors associated with stunting is essential for developing effective prevention strategies.Methods: This analytical cross-sectional study involved 30 children under five years of age selected using total sampling from the Kanigaran Community Health Center catchment area, Probolinggo City. Independent variables included maternal education, household income, exclusive breastfeeding, birth weight, history of infectious diseases, environmental sanitation, and parenting practices. Data were analyzed using the Chi-square test and multiple logistic regression.Results: Maternal education (p=0.027), household income (p=0.011), exclusive breastfeeding (p=0.037), birth weight (p=0.024), and history of infectious diseases (p=0.045) were significantly associated with childhood stunting. Household income was identified as the strongest predictor in the multivariable model (Adjusted OR=4.42; p=0.012).Conclusion: Childhood stunting is influenced by multiple socioeconomic and health-related factors, with household income being the strongest determinant. Integrated interventions addressing household economic conditions, maternal education, infant nutrition, and disease prevention are recommended to reduce childhood stunting.